TINJAUAN ATAS PENERAPAN APLIKASI E-FAKTUR 3.0 DAN PELAPORAN SPT MASA PAJAK PERTAMBAHAN NILAI PADA PT MEDKES GLOBAL PRIMA - Nur Afifah Azwani; Robert Pius Pardede (Jurnal Informatika Kesatuan, 2023)
Tax is one of the largest sources of income for Indonesia, which is used for the welfare of the Indonesian people. By paying taxes, Indonesian citizens are expected to be more orderly and responsible for their own country. Based on this, the role of the Director General of Taxes is very important as it is in charge of tax affairs and makes policies that can maximize tax revenue for the country. One of the policies of the Directorate General of Taxes is the Electronic Tax Invoice known as e-Faktur. This policy is implemented to avoid fictitious tax invoices made by taxpayers. This review aims to review and find out how the application of the e-Faktur 3.0 application as a tool for making Tax Invoices and Periodic SPTs for reporting Periodic VAT SPTs is carried out every month at PT Medkes Global Prima. The evaluation results in this study indicate that the application of the e-Faktur application to PT Medkes Global Prima as a whole is quite good and follows the applicable tax regulations although there are still some shortcomings regarding the minimum output tax so that the company always pays more, this indicates more burden excluded from the income at PT Medkes Global Prima.